Desinfeksi Nebulizer yang Terkontaminasi Klebsiella Pneumoniae untuk Pencegahan Ventilator-Associated Pneumonia (VAP) - Ariningpraja, Rustiana Tasya; Wisnasari, Shila; Lestari, Retno; Perkasa, Wendi Genta; Suwondo, Rifka Anindita (Journal of Telenursing (JOTING), 2024)
This study aims to evaluate the effectiveness of nebulizer disinfection contaminated with Klebsiella pneumoniae using one of the materials widely used in hospitals, chlorhexidine. The research method used in vitro experiments. K. pneumoniae was isolated from hospital samples and then multiplied for 24 hours. The nebulizer jet was then intentionally contaminated with K. pneumoniae and disinfected using chlorhexidine solution at various concentrations. The effectiveness of the disinfection process was then assessed using culture and calculated based on the number of colonies formed after the disinfection process. The results showed that chlorhexidine was effective in significantly reducing the number of K. pneumoniae colonies, especially at a concentration of 2.5%. The use of chlorhexidine as a routine disinfectant in pneumatic nebulizers could be an effective strategy in the prevention of VAP, thus improving safety in critically ill patients. This study supports the use of chlorhexidine as part of a disinfection protocol to reduce the incidence of VAP caused by K. pneumoniae. In conclusion, chlorhexidine is effective in reducing the number of K. pneumoniae colonies so that it can be a disinfectant to prevent Ventilator-Associated Pneumonia (VAP). Keywords : Disinfectant, Jet Nebulizer, Klebsiella pneumoniae, Ventilator-Associated Pneumonia